Squamous cell carcinoma in the elbow region with metastasis in a canine: a case report - Ferreira De Carvalho Felix, Alessandra Rosse (2022)
The study describes a case of squamous cell carcinoma (SCC) in the elbow region with metastasis in a canine. The patient, a 9-year-old Labrador female presented an ulcerated lesion in the right elbow region, with a six-month evolution and she underwent surgical removal. The diagnosis of SCC was obtained after histopathological evaluation. Chemotherapy was proposed, but the tutor refused. The patient remained in follow-up with the responsible physician. There was the appearance of metastases in various regions of the body after three months, so euthanasia was chosen.